Good practice guide indigenous peoples and mining. (International Council on Mining and Metals, 2010)
This guide provides mining companies with positive, practical and comprehensive approaches to develop successful relationships with indigenous peoples.
Title from eBook information screen.
Keywords: Mineral industries -- Developing countries.; Indigenous peoples -- Developing countries.; Indigenous peoples -- Economic conditions.; Land use -- Developing countries.; Mines and mineral resources -- Social aspects.; Developing countries.; elektronické knihy; electronic books